Suplementação hiperproteica vs suplementação hiperglicídica: impactos na recuperação do dano muscular após exercício de força excêntrica - Farias, Luana Souza de (2023)
Introduction: Eccentric training is considered one of the best methods for hypertrophy and strength gain. However, in the post-training period, there is an increase in muscle soreness and high protein degradation, which reduces posttraining muscle strength. Objective: To verify the influence of supplementation hyperprotein and hyperglycemic activity after eccentric training in markers of injury and muscle pain. Methodology: This is a case-by-case cross-sectional study.control, double-blind, randomized, crossover, where 15 men were measured (25.0±1.4 years; 83.4±2.2 kg; 11.5±3.6% body fat) physically trained in two different situations, where it was supplemented: diet hyperproteic – PRO (70% protein and 30% carbohydrate) and hyperglycemic diet – CHO (70% carbohydrate and 30% protein). To analyze muscle damage, serum levels of myoglobin (MYO), creatine phosphokinase (CPK), lactate dehydrogenase (LDH) and leukocytes (monocytes, neutrophils and lymphocytes). A maximum strength was estimated by the 10RMs test. Muscle soreness was estimated through a visual analogue scale. The intervention consisted of 5 sets of 10 repetitions in one exercise for upper limbs (bench press) and one for lower limbs (leg-press). Results: The tissue injury generated by the exercise session was verified, regardless of the treated group (CHO: 407.2 ± 96.6 vs 612.2 ± 104.7, p=0.0019; PRO: 415.5 ± 85.2 vs 591.1 ± 73.4, p=0.0004). On the other hand, 48h and 72h after the execution of the exercise, the supplementation of PRO reduced the levels of CK in 13.1%, (p=0.0408) and 19.72% (p=0.0001), respectively, compared to the CHO group at the same times; LDH, showed no difference between the types of treatments used in the study (p>0.05);Both subjects supplemented with CHO and PRO had an increase in PSD muscle after the eccentric exercise session in the order of 347.57% (p<0.0001) and 305.23% (p<0.0001). there was no statistical difference (p>0.05) in the muscle strength between groups supplemented with CHO and PRO at times analyzed. Conclusion: It was observed that eccentric exercise can generate muscle damage. At the same time, active male adults, when submitted to an eccentric training session, showed faster recovery from tissue injury when they consumed PRO supplement, where the reduction of CK and MYO markers was observed. Thus, food supplements are intended to supplement and improve the diet, optimize recovery during or after efforts and increase the necessary energy reserves.